Effect of Roasting Time In Microwave To Physical Quality Of Chicken Steak - Nazhar Vernanta. Billy Rasyad; Djalal Rosyidi; Arisi Sri Widati (Faculty of Animal Science Universitas Brawijaya, 2012)
The purpose of this research was to know effect of roasting time on chicken steak using microwave based on physical quality (pH, texture and WHC). The material of research was steak of broiler breast. The treatments of roasting time were 3 minutes (T3), 4 minutes (T4), 6 minutes (T6) and 10 minutes (T10). The experiment design of this research was with Completely Random Design (CRD). The data was analyzed by Analysis of variance (ANOVA) followed by least significanced Â there was significant differences between samples. The results showed that the roasting time for 10 minutes gave significant effect (P<0.01) on steak texture. Whilst the roasting time of 3 minutes, 4 minutes and 6 minutes gave no significant effect (P>0.05) on pH and WHC. It can be concluded that roasting time using microwave for 10 minutes was the best treatment to improve chicken steak texture and this may lead to produced good physical quality steak . Key words : Chicken steak, roasting time, physical quality